Rheological study of mixed flour: wheat (Triticum vulgare), barley (Hordeum vulgare) and potato (Solanum tuberosum) for use in the preparation of bread - Sandoval, Galo (2012)
With wheat flour imported and domestic wheat cereals produced in the country, and the potato tuber, a rheological study was performed to determine the most suitable proportions of substitution of wheat flour imported with the latter and its feasibility for making bread. We worked in mixtures of flour, wheat CWRS # 1 (red spring wheat in western Canada) Cañicapa barley flour, wheat and potato Cojitambo Gabriela, from Ecuadorian cultures in proportions of 10, 20 and 30% (p / p). Masses from mixtures of flours were analyzed on a Brabender Farinograph, in order to determine the water absorption, development time, stability and rate of tolerance with a view to selecting the flour blends that have a behavior similar to CWRS wheat flour # 1. The best mixtures found were: wheat flour # 1 CWRS replaced with 10, 20 and 30% barley flour Cañicapa, and the mixture of wheat flour # 1 CWRS wheat flour in Cojitambo 30%. These flour mixes selected were also subjected to rheological analysis of their masses using a computer Mixolab. The breads made from flours selected were evaluated in a sensory panel. The breads more accepted by consumers were those containing 20 and 30% barley, followed by the group of those made with imported wheat with 30% wheat Cojitambo, and containing 10% of barley flour.